Architecture in Bali between two worlds: integrating tradition and modernity in the age of globalization - Schmitt, Lukas (Journal of A Sustainable Global South, 2025)
This paper explores how Balinese architecture adapts to globalization pressures by blending traditional architectural elements with modern sustainable practices. Using Tzonis and Lefaivre’s theory of critical regionalism as a framework, the study examines eco-resorts in Bali as case studies of sustainable tropical architecture that respect cultural heritage while addressing the demands of an international tourism industry. Through these examples, the analysis evaluates how the combination of traditional Balinese design principles with contemporary innovations has achieved sustainable development within the eco-tourism context.